Efficiency in Cloud Computing through Serverless and Green Computing based on Microarchitecture - Fahira, Fahira; Awangga, Rolly Maulana; Gopikrishnan, Sundaram (Journal of Information Technology and Cyber Security, 2024)
PT Pelindo Multi Terminal is a subholding of PT Pelabuhan Indonesia (Persero), a State-Owned Enter-prise (SOE). PT Pelindo Multi Terminal carries out Kesehatan dan Keselamatan Kerja (K3) or Occupa-tional Health and Safety (OHS) monitoring, which currently still uses manual methods with paper. This method causes problems, such as delays in decision making and the inability to monitor events in real-time. This research aims to overcome these problems by proposing an application called "Portsafe+". Portsafe+ is developed using microservices architecture and micro frontend, with Progressive Web Apps (PWA) as the interface and Google Cloud Function as the backend. Portsafe+ was tested by measuring the response speed of the backend that responds to each request. The test results show that this application improves the response speed with 99% execution time of 880.37 ms. Based on the test results, Portsafe+ successfully overcomes the existing problems. The application of PWA technol-ogy facilitates access and improves the efficiency of OHS management compared to the previously used paper-based manual system.